Protein Science Encyclopedia 2008
DOI: 10.1002/9783527610754.sf11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations to Study Protein Folding and Unfolding

Abstract: Originally published in: Protein Folding Handbook. Part II. Edited by Johannes Buchner and Thomas Kiefhaber. Copyright © 2005 Wiley‐VCH Verlag GmbH & Co. KGaA Weinheim. Print ISBN: 3‐527‐30784‐2 The sections in this article are Introduction Molecular Dynamics Simulations of Peptides and Proteins Folding of Structured Peptides Reversible Folding and Free Energy Surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 152 publications
0
6
0
Order By: Relevance
“…The use of robust statistical methods as outlined in the supporting materials have allowed us to systematically compare and document the effects of force field selection on the sampled conformational space of the inherently disordered protein Aβ(1–40) dimer in water at physiological temperature (310 K). Although, atomistic MD simulations have even been able to accurately predict the folded state of globular proteins, intermediate states are not consistent with experimental data and simulations have been unable to accurately reproduce melting curves and other temperature dependent behavior . The problems of inaccurate prediction of intermediate folded states and poor reproduction of melting curves arises from the overestimation of the steepness of the potential energy basins for protein‐protein interactions .…”
Section: Discussionmentioning
confidence: 99%
“…The use of robust statistical methods as outlined in the supporting materials have allowed us to systematically compare and document the effects of force field selection on the sampled conformational space of the inherently disordered protein Aβ(1–40) dimer in water at physiological temperature (310 K). Although, atomistic MD simulations have even been able to accurately predict the folded state of globular proteins, intermediate states are not consistent with experimental data and simulations have been unable to accurately reproduce melting curves and other temperature dependent behavior . The problems of inaccurate prediction of intermediate folded states and poor reproduction of melting curves arises from the overestimation of the steepness of the potential energy basins for protein‐protein interactions .…”
Section: Discussionmentioning
confidence: 99%
“…Ferrara and Caflisch utilized MD simulation to study the reversible folding and free energy surface of two designed 20-residue sequences called beta3s (TWIQNGSTKWYQNGSTKIYT) and D PG (Ace-VFITSDPGKTYTEVDPG-Orn- KILQ-NH). Both of these sequences have a three-stranded antiparallel β -sheet topology ( 44 , 84 ). The beta3s have been examined previously by Nuclear Overhauser enhancement spectroscopy and chemical shift data, both of which showed that at 10°C, beta3s populates a single structured form-the three-stranded antiparallel β -sheet conformation with turns at Gly6-Ser7 and Gly14-Ser15 ( 44 , 85 ).…”
Section: Simulation Applicationsmentioning
confidence: 99%
“…They provide an opportunity to study the physical characteristics of systems that are not easily examined in the laboratory ( 43 ). For example, there is active research aimed toward enhancing the MD algorithms, so they may simulate protein folding and unfolding ( 44 48 ). In addition to biological applications, MD simulations have been used to study the physical characteristics of non-biological nanoparticles ( 49 ).…”
mentioning
confidence: 99%
“…Due to the complexity of biological and nonbiological systems, MD simulations have come under great interest for their ability to predict and verify experimental results, providing an opportunity to study the physical characteristics of systems that are not easily examined in the laboratory. Research aimed at improving MD algorithms so that they can simulate the folding and unfolding of proteins is one example of the study of these features. , In addition to biological applications, MD simulations have been used to study the physical characteristics of nonbiological nanoparticles . Comparisons of simulation and experimental data serve to test the accuracy of the calculated results and provide criteria for improving the methodology .…”
Section: Molecular Dynamics Simulations: Challenges and Opportunitiesmentioning
confidence: 99%